Evaluation of factors influencing acceptance of HPV vaccination among adolescents and young adults: contribution of a nurse - Veselinovic, Violeta; Pazun, Vanja; Trbovic, Verica; Maricic, Milena (Education and Research in Health Sciences, 2023)
This review article assesses the factors influencing the acceptance of the HPV vaccine among adolescents and young adults, with a special focus on the contributions of nurses. HPV is a significant public health concern that can have serious health consequences, such as cervical cancer, genital warts, and other complications. However, vaccination can significantly reduce the risk of these diseases.The aim of the review was to investigate the factors influencing the acceptance of the HPV vaccine among adolescents and young adults, with a emphasis on the contribution of healthcare professionals. The analysis of studies' results indicates the complexity of factors influencing the decision to receive the HPV vaccination. Nurses have an unequivocal contribution in educating and supporting adolescents and their parents. Studies have shown that nurses are often the most important source of information about HPV vaccination, which contributes to increased awareness and positive attitudes towards vaccination. Furthermore, parents, friends, and social networks also have a significant influence on adolescents' vaccination decisions. Social networks also contribute to shaping attitudes about HPV vaccination, with positive and negative content having different effects.Public campaigns and health education are also specific factors in increasing awareness and acceptance of HPV vaccination. Studies have shown that the selection of appropriate health education methods is crucial for success in raising awareness and acceptance of vaccination. These results suggest that effective campaigns and educational programs are essential for vaccination promotion.Understanding the factors influencing the acceptance of the HPV vaccine among adolescents and young adults requires a comprehensive approach that involves nurses, parents, friends, social networks, and public campaigns. Only through collective efforts can we achieve an increase in vaccination rates, which is crucial for protecting the health of young people from HPV infection and its serious consequences.
Keywords: HPV vaccine; adolescents; young adults; acceptance factors; social networks; health education